2020
DOI: 10.3349/ymj.2020.61.5.359
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA LINC00313 Knockdown Inhibits Tumorigenesis and Metastasis in Human Osteosarcoma by Upregulating FOSL2 through Sponging miR-342-3p

Abstract: Purpose: Osteosarcoma (OS) is the most common primary bone tumor, with high morbidity in infants and adolescents. Long noncoding RNA LINC00313 has been found to modulate papillary thyroid cancer tumorigenesis and to be dysregulate in lung cancer. However, the role of LINC00313 in OS has not yet been addressed. Materials and Methods: We evaluated mRNA and protein expression using real-time quantitative PCR and Western blotting. Cell proliferation was evaluated using MTT; apoptosis and autophagy were assessed wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…In the present study, we performed data mining using public databases to show that LINC00313 expression was upregulated significantly in TGCT tissue and that there was significantly association between DFI survival and LINC00313 expression. This is similar to the findings of another research team in osteosarcoma [ 27 ] and cervical carcinoma [ 28 ], who found that patients with high LINC00313 expression had poorer overall and disease-free survival. Moreover, the expression of LINC00313 has a good diagnostic value for TGCT.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In the present study, we performed data mining using public databases to show that LINC00313 expression was upregulated significantly in TGCT tissue and that there was significantly association between DFI survival and LINC00313 expression. This is similar to the findings of another research team in osteosarcoma [ 27 ] and cervical carcinoma [ 28 ], who found that patients with high LINC00313 expression had poorer overall and disease-free survival. Moreover, the expression of LINC00313 has a good diagnostic value for TGCT.…”
Section: Discussionsupporting
confidence: 90%
“…For example, LINC00313 was reported to be highly expressed in lung cancer and to indicate shorter overall survival (OS) [ 26 ]. High expression of LINC00313 was associated with shorter OS in osteosarcoma [ 27 ]. To the best of our knowledge, the expression and role of LINC00313 in TGCT has not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the lncRNA Sox2OT-V7 regulates ULK1, ATG4A, and ATG5 through miR-142/miR-22 to modulate autophagy in osteosarcoma cells (Zhu et al, 2020). The lncRNA LINC00313 acts as a sponge for miR-342-3p, regulating FOSL2 levels and inhibiting autophagy in human osteosarcoma cells, ultimately suppressing osteosarcoma cell metastasis (Chen et al, 2020). LncRNA-ATB modulates autophagy in liver cancer cells by activating Yes-associated protein (YAP) and inducing ATG5 expression, associated with poor prognosis of liver cancer patients (Wang C.Z.…”
Section: Introductionmentioning
confidence: 99%
“…MiR-342-3p could repress colorectal cancer chemoresistance [ 25 ], and could act synergistically with miR-205-5p to reduce tumor chemoresistance by inhibiting E2F1 [ 26 ]. MiR-342-3p had an obvious tendency of low expression in OS, and has been proved to inhibit the progression and promote the radiosensitivity of OS [ 27 29 ]. Our study discovered that miR-342-3p was underexpressed in the DXR-resistant OS tissues and cells, and it also hindered OS DXR resistance.…”
Section: Discussionmentioning
confidence: 99%